Analisis Hubungan Pemberian Asi Eksklusif dan Pendidikan Ibu terhadap Perkembangan Bayi di Kota Pekanbaru - Siagian, Dewi Sartika; Herlina, Sara (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Breast Milk (ASI) is indispensable during infant growth and development. WHO has recommended for exclusive breastfeeding for up to 6 months without providing complementary foods and continued for up to 2 years accompanied by complementary foods. The purpose of this study was to determine the relationship of exclusive breast feeding and maternal education on infant development. This study is quantitative analytic observational with cross sectional design with a large sample of 83 people. The sampling method used is proportional sampling. Data analysis was done unvaried and bivariate. Univariate analysis showed that most of the infants received exclusive breastfeeding as much as 46 people (55.4 percent), low education as many as 56 people (67.5 percent) and most normal development of 47 people (56.6 percent). The result of bivariate analysis of exclusive breastfeeding on infant development with chi square test obtained value of P value less than 0,000 means there is relation between exclusive breast feeding to infant development and bivariate analysis of mother education on infant development with chi square test obtained value of P value 0,012 meaning there is a relationship between maternal education on infant development. Keywords: Exclusive Breast milk, Mothers Education, Infant Development